INHIBITING FACTORS FOR MAHASISWA SANTRI OF ENGLISH LANGUAGE EDUCATION PROGRAM IN COMPLETING UNDERGRADUATE THESIS - Wibowo, Joko (Jurnal Tinta, 2024)
The study aimed to reveal the inhibiting factors of Mahasiswa Santri in the English Language Education Program from accomplishing their undergraduate theses. It also aimed to identify their unique challenges, enable appropriate support programs and policies, improve graduation rates, contribute to knowledge of religious identity with academic commitment, and improve academic and religious success. Most previous studies focused their subjects on college students in general and did not distinguish significantly between Mahasiswa Santri and Non-Mahasiswa Santri. In contrast, this study focused on the Mahasiswa Santri as the subject of the research. However, the sample was only 9 students of Mahasiswa Santri, the other 19 were Non-Mahasiswa Santri. It applied two instruments: structured interviews and closed-ended questionnaires which Experts had validated. The research revealed that internal factors, such as time management and motivation, as well as external factors like the unavailability of the Internet and references, played crucial roles in inhibiting thesis completion. Time management was consistently identified as the most significant factor that inhibited undergraduate thesis writing. These findings emphasized the demand for improved support and resources to assist Mahasiswa Santri in resolving these inhibiting factors and accomplishing their theses. Keywords: Inhibiting Factors, Mahasiswa Santri, English Language Education Program, Undergraduate Thesis Completion